KONTEKS HISTORIS PRAKTEK HUMAS DI INDONESIA - I Gusti Ngurah Putra (Jurnal Ilmu Komunikasi, 2008)
As a part of management function public relations has been practiced in Indonesia since the Independence day. The development of public relations practice in Indonesia is influenced, among other things, by political system, government policies and economic development. As Indonesian political system is becoming more democratic, organizations are required to apply the symmetrical public relations models as suggested by Grunig.